Water management : water quality of rivers in Kuala Pilah (a case study) - Sulong, Mohamad Azmi (2000)
Kuala Pilah is a district situated in the middle of Negeri Sembilan. It's hilly and highly dense forested area makes it suitable as catchment areas to provide a continual water supply. The upstream has a relatively good water quality compared to the downstream. In this study, the water quality index for Muar River and Pilah River in Kuala Pilah district have been determined using five parameters namely BOD5, COD, ammoniacal nitrogen, total suspended solids and pH values. Other determinants for water quality are the nutrients content such as nitrates and phosphates and metals content such as iron and manganese. The water quality in the upper Muar River Basin that constitutes the rivers mentioned above has changed drastically when the rivers go through towns, industrial and housing or residential areas. Data collected from various sources and for several years show a continual deterioration of water quality in the basin since 1992 where the river water is polluted. The water quality is between Class IIA and Class III for those years. The high pollution in the rivers was due to the wastewater being discharged directly into the river without any treatment. Other contributors to the pollution are active logging and earthworks for development purposes. Hence, new approaches to management of water are introduced to uplift the water quality.